Implementation of Innovation in Integrated Evaluation and Learning System using Outcome-Based Education Ecosystem - I Gede Susrama Mas Diyasa; Ni Made Ika Marini Mandenni; Mohammad Rafka Mahendra A; Rangga Laksana A; I Nyoman Dita Pahang Putra (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: Outcome-Based Education is a learning method that focuses on the output which is learning achievements. Identification and determination of the achievements is a critical point for OBE due to the methods which will affect the learning and assessment planning. The main reason for this research is to give an innovation on this system which will be implemented. Design/methodology/approach: The implementation is done by integrating three processes; curriculum design, assessment, and learning methods. Findings: OBE utilizes knowledge aspects, skills, and attitudes based on the situation of the social, economic, and academic culture. This system also synergizes four types of users Admin, Curriculum Team, Lecturer, and Students. By adopting the methods and outcome-based learning, the system achieved simplicity for the users and improved the student's knowledge of its subjects. Paper type: Research paper